EVALUATING STUDENTS CREATIVE THINKING ABILITY IN WRITING NEGOTIATION TEXTS: A STUDY OF TENTH GRADE HIGH SCHOOL STUDENTS - Vardila, Helvina (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study evaluates the creative thinking ability of tenth grade high school students SMA class X in writing negotiation texts. This ability is crucial for generating original ideas and innovative solutions, demanding logical arguments, an understanding of perspectives, and mutual solutions. Using a qualitative descriptive approach, data were obtained through an analysis of negotiation texts. Aspects evaluated include fluency, flexibility, originality and elaboration of ideas. Results indicate that students creative thinking ability is generally sufficient, showing good fluency and flexibility, but requiring improvement in originality and idea elaboration. The implication is that creative thinking exercises need to be more integrated into the curriculum, especially in Negotiation Text material, to enhance effective and innovative communication.